Exploring Pragmatic Functions: A Speech Act Analysis of Conversations among Elementary School Students Using Articulate Storyline to Enhance English Speaking - Mungkap Mangapul Siahaan; Rudi Hartono; Yuliati (Journal of Education and Teaching Learning, 2026)
The increasing integration of digital tools in education prompts questions about their effectiveness in enhancing key language skills, particularly pragmatic competence. Pragmatic competence refers to the ability to use language appropriately in various social contexts, a skill crucial for effective communication. Despite the growing integration of technology in language learning, there remains a gap in developing students’ ability to use language appropriately in real-life interactions, particularly in non-native English contexts. Purpose: This study aims to investigate the role of Articulate Storyline, an interactive digital tool, in enhancing pragmatic competence among elementary school students (ages 10-12) in Indonesia. Specifically, it investigated how Articulate Storyline can stimulate students’ use of speech acts (locutionary, illocutionary and perlocutionary acts) in real-word communication settings such as the classroom, library and garden. Research Methodology: The study employed a descriptive qualitative research design, using speech act theory as a framework to analyse the pragmatic functions in students’ conversations. Data was collected from 125 students who engaged with Articulate Storyline in their English language lessons. Conversations were transcribed and analysed to identify the frequency and types of speech acts used in different contexts. The study focuses on how students utilize language in both structured (classroom) and informal (library, garden) settings. Findings: It is indicated that Articulate Storyline significantly enhanced students’ pragmatic competence especially in personal experiences. Conclusion: The study also revealed that conversational context (formal vs informal) played a crucial role in shaping types of speech acts, collaborative, critical and learning engagement.